The Moderating Role of Firm Size in the Relationship Between Tax Avoidance and Disclosure Practices - Bunga Tiara; Fajar Nurdin (E-Jurnal Akuntansi, 2025)
This study aims to examine the influence of profitability, inventory intensity, and thin capitalization on tax avoidance, while also assessing the moderating role of company size in these relationships. The research sample consists of 54 manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Data analysis is conducted using EViews 12 software, employing a quantitative research methodology with a descriptive approach. The findings indicate that profitability and inventory intensity have a significant effect on tax avoidance, whereas thin capitalization does not. Additionally, company size moderates the relationship between profitability and tax avoidance, as well as between thin capitalization and tax avoidance. However, company size does not moderate the relationship between inventory intensity and tax avoidance. These results provide valuable insights into the